BANK OF RUSSIA’S EXCHANGE RATE POLICE AND OPTION OF EXCHANGE RATE REGIME - VALENTINA VIL’EVNA Kuznetsova (Мир новой экономики)
The article devotes to such issues as the Russian current exchange rate police, the affected to exchange rate regime option factors, currency interventions, and aiming to smoothing extreme exchange rate volatility measures. The author supposes that the Russian exchange rate police needs to be radically changed.